The Influence of Store Atmosphere and Taste on Consumer Repurchase Interest in Bofet Mas Nur Solo Lohong Pariaman City - Patria Nagara; Rini Afrianti; Dorris Yadewani; Risma Yuwinda; Faris Ramadhan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the effect of the store atmosphere and taste of consumer repurchase interest in bofet mas nur solo lohong pariaman city, so that this study can run the author distributed questionnaires to 60 consumers who bought and became customers at Mas Nur Solo Lohong. This study used 2 methods, namely descriptive analysis method and st atistic analysis method with the help of SPSS version 23. The descriptive analysis method in this study is a description of the data results that have been obtained by the author, while the statistical analysis method, which is used to conduct multiple linear analysis and test research hypotheses.The results of this study store atmosphere and taste on consumer repurchase interest have a significant effect. Store atmosphere has a regression coefficient value of 0.442 with a count t value of 3.480 > t table of 1.672 and a significant value of 0.0 01 smaller than the level of significant of 0.05, then taste has a regression coefficient value of 0.518 with a value of t count 3.348 > ttable 1.672 and a significant value of 0.0 01 smaller than the level of significant, and simultaneously a calculated F value = 32.255 with sig = 0.000 < 0.05.Store atmosphere and taste have a significant influence on consumer repurchase interest in bofet mas nur solo lohong pariaman city, the result of the coefficient of determination is known that the coefficient of determination is R = 0.729 with an R2 = 0.531, this means 53.1,% repurchase interest Consumers can be explained by variables of store atmosphere and taste while the remaining 46.9% is influenced by other variables that are not included in this study.